2017
DOI: 10.21786/bbrc/10.4/2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some biological properties of Saussurea costus crude root extract

Abstract: The current study aimed to evaluate some biological activities of Saussurea costus (S. costus) such as phytochemical constituents, antimicrobial activity and antifeedant potential on the larvae of Spodoptera littoralis. The results revealed that the methanol extract of roots of S. costus are rich in some bioactive phytochemical compounds such as alkaloids, phenols/polyphenols, fl avonoids, terpenoids, tannins, coumarins, quinines, steroids, cardiac glycosides and resins. The antimicrobial screening revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…On the other hand, some plants chosen by the population are inspired from Islamic medicine such as Black cumin, ginger, and Indian costus, which is the case of other Muslim countries (Alqethami, et al 2017;El Sayed, et al 2020;Sheikh 2016). Some authors have reported that the Muslim societies are interested in the remedies mentioned in prophetic medicine (Aati, et al 2019;Alqethami, et al 2017) such, N. sativa (Maideen 2020), A. costus (Abdallah, et al 2017), honey (El Sayed, et al 2020, Z. officinale, and olive oil (Mehmood, et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some plants chosen by the population are inspired from Islamic medicine such as Black cumin, ginger, and Indian costus, which is the case of other Muslim countries (Alqethami, et al 2017;El Sayed, et al 2020;Sheikh 2016). Some authors have reported that the Muslim societies are interested in the remedies mentioned in prophetic medicine (Aati, et al 2019;Alqethami, et al 2017) such, N. sativa (Maideen 2020), A. costus (Abdallah, et al 2017), honey (El Sayed, et al 2020, Z. officinale, and olive oil (Mehmood, et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial efficacy of Doum fruits methanol extract against the clinical strains was evaluated using an agar well diffusion assay 16 . Plates containing Nutrient agar (NutriSelect® Plus, Merck, USA) was made by pouring 25 mL of autoclaved medium into sterile plates (90 mm in diameter) and left for up to 15 minutes until solidified at room temperature.…”
Section: Agar Diffusion Methodsmentioning
confidence: 99%
“…Agar well diffusion method was used to evaluate the possible antimicrobial activity of Doum fruits methanolic extract [13]. Prior to the experimental phase, microorganisms were subcultured in a broth medium and incubated overnight for bacteria and for 48 hours for fungi to get microbes at the exponential phase.…”
Section: Well Diffusion Methodsmentioning
confidence: 99%